Classical and nonclassical class I major histocompatibility complex molecules exhibit subtle conformational differences that affect binding to CD8alphaalpha. - Gao, G; Willcox, B; Wyer, JR; Boulter, J; O'Callaghan, C; Maenaka, K; Stuart, D; Jones, E; Van Der Merwe, P; Bell, J; Jakobsen, B (2000)
The cell surface molecules CD4 and CD8 greatly enhance the sensitivity of T-cell antigen recognition, acting as "co-receptors" by binding to the same major histocompatibility complex (MHC) molecules as the T-cell receptor (TCR). Here we use surface plasmon resonance to study the binding of CD8alphaalpha to class I MHC molecules. CD8alphaalpha bound the classical MHC molecules HLA-A*0201, -A*1101, -B*3501, and -C*0702 with dissociation constants (K(d)) of 90-220 microm, a range of affinities distinctly lower than that of TCR/peptide-MHC interaction. We suggest such affinities apply to most CD8alphaalpha/classical class I MHC interactions and may be optimal for T-cell recognition. In contrast, CD8alphaalpha bound both HLA-A*6801 and B*4801 with a significantly lower affinity (>/=1 mm), consistent with the finding that interactions with these alleles are unable to mediate cell-cell adhesion. Interestingly, CD8alphaalpha bound normally to the nonclassical MHC molecule HLA-G (K(d) approximately 150 microm), but only weakly to the natural killer cell receptor ligand HLA-E (K(d) >/= 1 mm). Site-directed mutagenesis experiments revealed that variation in CD8alphaalpha binding affinity can be explained by amino acid differences within the alpha3 domain. Taken together with crystallographic studies, these results indicate that subtle conformational changes in the solvent exposed alpha3 domain loop (residues 223-229) can account for the differential ability of both classical and nonclassical class I MHC molecules to bind CD8.